Упреждающая адаптация курсантов военного факультета к новым условиям жизнедеятельности - Bantyukova Елена (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article is devoted to the proactive adaptation of students to the new conditions of professional activity. The notion of the concept of «anticipatory adaptation» is disclosed in accordance with the psychological-pedagogical and systemic approaches. We formulate, analyse, forecast and solve the tasks on the organization of special psychological and pedagogical support of cadets in the new conditions of life activity by means of education. Particular attention is paid to forecast of anticipatory adaptation and the need to conduct at all stages of preporatory training.